3D-printing of segregated carbon nanotube/polylactic acid composite with enhanced electromagnetic interference shielding and mechanical performance. (1st January 2021) - Wang, Yan; Fan, Ze-Wen; Zhang, Hong; Guo, Jing; Yan, Ding-Xiang; Wang, Shengfa; Dai, Kun; Li, Zhong-Ming
Abstract: Construction of segregated structures within conductive polymer composites (CPCs) is a prospective strategy to enhance electromagnetic interference (EMI) shielding effectiveness (SE). However, the CPCs of segregated structures frequently experience worsened mechanical performances due to weak interface reactions between adjacent polymer domains, which are hindered by conductive fillers. Herein, 3D-printed segregated carbon nanotube (CNT)/polylactic acid (PLA) composite was firstly exploited to develop high mechanical properties while achieving good performance for electromagnetic interference shielding. Within the final 3D-printed CNT/PLA composite, CNTs coated on 3D-printed PLA scaffold were translated to interconnected conductive network after compression. Thus, EMI SE of composite was as high as 67.0 dB when 5.0 wt% CNTs were loaded. Furthermore, 3D-printed PLA scaffold with a highly continuous structure also benefited the mechanical robustness of the segregated composite, revealing the bending strength (87.8 MPa) and Young's modulus (4.43 GPa), which were 101% and 43% higher than 43.7 MPa and 3.08 GPa for the conventional CNT/PLA composite. Moreover, the regulation of 3D-printed PLA scaffolds results in promising CNT/PLA composites with tunable EMI SE. This work suggests that 3D printing technology is an effective and easy approach to develop the outperformance of CPCs for different radiation source fields and electronic devices. Graphical abstract: Unlabelled Image Highlights: 3D-printing technology was exploited to construct segregated conductive polymer composites for electromagnetic interference shielding. The segregated structures endow high mechanical properties and good performance of electromagnetic interference shielding. Electromagnetic interference shielding effectiveness is tunable by controlling the 3D-printed polylactic acid scaffolds.